Комп’ютерна система управління багатоканальними освітлювальними пристроями - Бомчик, О. С.; Парамуд, Я. С.; Bomchyk, O.; Paramud, Y. (Видавництво Національного університету “Львівська політехніка”, 2018)
Розглянуто проблему побудови комп’ютерної системи управління багатоканальними освітлювальними пристроями. Визначено базові засоби систем управління освітленням. Розроблено узагальнену структуру комп’ютерної системи управління багатоканальними освітлювальними пристроями. Обґрунтовано доцільність застосування в таких системах магістральних послідовних інтерфейсів. Проаналізовано і обґрунтовано ефективність застосування протоколу DMX. Розглянуто структурну схему системи управління багатоканальними освітлювальними пристроями за таким протоколом та загальний алгоритм роботи системи.

The problem of controlling the computer control system of multichannel lighting devices is considered. Basic means of lighting control systems are determited. Generalised structure system for controlling of multichannel lighting devices is developed. Expediency of use of trunk serial interfaces in such systems is substantiated. Efficiency of use of DMX protocol is subsnantiated and analysed. The structural scheme of multichannel lighting devices control system according to such a protocol and the general algorithm of system operation are considered. The analysis and justification of the choice of application of the protocol dmx 512 was made. The structural scheme of the system and the general algorithm of the system work are considered.
Computer system management by multiple channel lighting equipment
Keywords: комп’ютерна система; багатоканальні освітлюючі пристрої; протокол; computer system; multichannel illuminating devices; protocol; 621